Themes and Thematic Progression ELT Forum-JET Journal Articles (Universitas Negeri Semarang, 2021)
This research aims to identify the types of Themes and Thematic Progressions in the daily posts raised by the ELT Forum-JET UNNES, to analyze Constant theme patterns, Zig-zag patterns, and Multi-Theme patterns that create Themes and Thematic Progressions. It is used in the daily posts raised by the UNNES ELT-JET Forum, To describe the methods and consistency used in improving reading in the daily posts by the UNNES ELT-JET Forum. In analyzing the development of reading in daily posts, researchers only focus on the introductory paragraph because most people describe general topics in that section, which is where the essence of the daily post will explain in that section. It is a descriptive qualitative design. Researchers analyzed thematic growth to investigate the thematic progress type in student daily posting reading, describe the realization of thematic progress in student daily reading writing, and determine the alibi of using thematic growth in student reading writing. Sources of information are from reading research proposals made by students majoring in English at specific academies. This research will focus on assessing students' daily posts published in the ELT Forum-JET (Unnes Journal of English Teaching). The subjects of this research were 3 S1 students at Semarang State University. They majored in learning English. Based on research results is about thematic growth in daily posts. As determined by Eggins, themes, and poems are classified into three types; KTP, SLP, and DTP. Researchers did not explain the classification of themes and rhemes in this research because the main point is the development of themes. Based on the results of the information that the researchers collected, the students' method of compiling themes and rhymes in their journal posts is as follows. Most of their writings are Fair and Poor levels. There is no consistency in just one thematic development. There are no readings that do not have a thematic development pattern. The author arranges themes and rhemes in his journal posts found through several interview questions described above. The participants of this research were three students who had already graduated. Based on the results of the information that the researchers collected, the students' method of compiling themes and rhymes in their journal posts is as follows. Most of their writings are Fair and Poor levels. There is no consistency in just one thematic development. There are no readings that do not have a pattern of thematic development.